Anonymous

# (Boolean Algebra) Prove that xy + xy = (x+y)(x+y )?

Update:

Prove that xy + xy' = (x+y)(x+y' )

Update 2:

Sorry, the question header didn't format the question properly. Please look at the description

### 1 Answer

Relevance

- AshLv 73 months agoBest Answer
LHS = xy + xy'

= x(y + y') ..........distributive law

= x(1)

= x

RHS = (x+y)(x+y' )

= x+(yy') ...........distributive law

= x+(0) .............complement law

= x

LHS = RHS

Still have questions? Get your answers by asking now.